Rule of Nahwiyah Variations in Arabiyah Bayna Yadaik Book and its Contribution on Arabiyah Asasiyah Subject - Maman Abdurrahman (Intelektual Pustaka Media Utama, 2015)
This research is motivated by the need of an innovative teaching module and as a way to facilitate students to understand Nahwu. This research’s purpose is to describe about Nahwu subject as presented in the First Arabiyah bayna Yadaik Book Volume 2 and its contribution to Arabiyah Asasiyah subjects in Arabic Education Department, Faculty of language and literature education, UPI. This research used a qualitative approach of Content Analysis with sources data from the First Arabiyah Bayna Yadaik Book Volume 2 and Arabiyah Asasiyah Syllabus which used to being learnt in Department of Arabic Language, Faculty of language and literature education, UPI in 2014/2015 academic year. The results are obtained by discovering of nahwu subjects with simple presented, such as tarkib isnadi, tarkib idhafi, tarkib washfi, tarkib ‘athfi, jumlah ismiyah, and jumlah fi’liyah with full exercises, it is going to contribute Arabiyah Asasiyah subject that contains simple and easy to understand material about Nahwu subjects